MEMAKNAI INTERAKSI LINTAS BAHASA DAN BUDAYA DALAM KONTEKS LOKAL - Masduki Masduki (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2010)
Implemeting culture and language can be interpreted in terms of conducting observable activities in natural settings or responding/reacting toward the certain situation in accordance with what the doers or speakers do. In interpreting this culture, it can not be avoided from emerging any problems since the implementation involves any other practical value and habits which sometimes can not be observed. The problems becoming so serious whether the doers are demanded to adopt new culture placed directly opposite to their own value and habits. The problems will in the long run emerge as a culture shock. This article highlights the ways of understanding some conviction and cases happened in certain situation or local culture. Understanding this cross culture and language interaction will hopefully contribute a new discourse in specific contexts.